Measuring Vowel Duration Variability in Native English Speakers and Polish Learners - Porzuczek, Andrzej (Research in Language, 2012)
This paper presents a set of simple statistical measures that illustrate the difference between native English speakers and Polish learners of English in varying the length of vocalic segments in read speech. Relative vowel duration and vowel length variation are widely used as basic criteria for establishing rhythmic differences between languages and dialects of a language. The parameter of vocalic duration is employed in popular measures such as ΔV (Ramus et al. 1999), VarcoV (Dellwo 2006, White and Mattys 2007), and PVI (Low et al. 2000, Grabe and Low 2002). Apart from rhythm studies, the processing of data concerning vowel duration can be used to establish the level of discrepancy between native speech and learner speech in investigating other temporal aspects of FL pronunciation, such as tense-lax vowel distinction, accentual lengthening or the degree of unstressed vowel reduction, which are often pointed out as serious problems in the acquisition of English pronunciation by Polish learners. Using descriptive statistics (relations between personal mean vowel duration and standard deviation), the author calculates several indices that demonstrate individual learners' (13 subjects) scores in relation to the native speakers' (12 subjects) score ranges. In some tested aspects, the results of the two groups of speakers are almost cleanly separated, which suggests not only the existence of specific didactic problems but also their actual scale.